2019
DOI: 10.1162/jocn_a_01341
|View full text |Cite
|
Sign up to set email alerts
|

Subgoal- and Goal-related Reward Prediction Errors in Medial Prefrontal Cortex

Abstract: A longstanding view of the organization of human and animal behavior holds that behavior is hierarchically organized—in other words, directed toward achieving superordinate goals through the achievement of subordinate goals or subgoals. However, most research in neuroscience has focused on tasks without hierarchical structure. In past work, we have shown that negative reward prediction error (RPE) signals in medial prefrontal cortex (mPFC) can be linked not only to superordinate goals but also to subgoals. Thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 32 publications
3
14
0
Order By: Relevance
“…Consistent with our caudate responses reflecting a model-based updating process, a previous fMRI study of navigation in a continually changing environment found that caudate activity correlated with parameters of a model-based representation of the environment (Simon & Daw, 2011;Dickinson & Balleine, 2002). More recently, caudate activity has been shown for events where pauses were implemented, as well as when there were unexpected changes in distance (Ribas-Fernandes, Shahnazian, Holroyd, & Botvinick, 2019).…”
Section: The Role Of Pfc Hippocampus and Caudate In Responding To Dsupporting
confidence: 88%
“…Consistent with our caudate responses reflecting a model-based updating process, a previous fMRI study of navigation in a continually changing environment found that caudate activity correlated with parameters of a model-based representation of the environment (Simon & Daw, 2011;Dickinson & Balleine, 2002). More recently, caudate activity has been shown for events where pauses were implemented, as well as when there were unexpected changes in distance (Ribas-Fernandes, Shahnazian, Holroyd, & Botvinick, 2019).…”
Section: The Role Of Pfc Hippocampus and Caudate In Responding To Dsupporting
confidence: 88%
“…This model learned the values of different options (whether to navigate using an egocentric or allocentric frame of reference), where each option corresponded to sequences of low-level movements in the maze. This conceptualization aligns well with increasing evidence that ACC is sensitive to hierarchically-organized action representations [27] and reward signals [28,29]. It is also consistent with observations that ACC supports foraging behavior [30], which is naturally framed as a hierarchical problem.…”
Section: Hierarchysupporting
confidence: 86%
“…These results support the hypothesis that prefrontal-hippocampal representations organize relational knowledge-in this case for spatial navigation-at different scales of generalization and abstraction (Behrens et al, 2018;Momennejad & Howard, 2018) . In the case of spatial navigation, this hierarchical representation in turn enables hierarchical planning and subgoal computation using graphs of the environment (Figure 1) abstracted at different scales (Ribas-Fernandes et al, 2018) . Our proposal is that planning at larger scales may be enabled by larger and more abstract scales of predictive representations in anterior PFC (Figure 1, large scale graph).…”
Section: Discussionmentioning
confidence: 99%